Strategi Coping Orang Tua Yang Memiliki Anak Autis - Nisa, Zain Nur Choirul, Setia Asyanti S.Psi, M.Si (2017)
Patients of autism each year has increased, the number of autistic in Indonesia reached 112,000 inhabitants (Priherdityo, 2016). Parents who have children with autism tend to be more feeling stressed and depressed because it has an important role in handling and parenting an autistic child. The purpose of this study is to describe the strategy of coping with parents who have a child with autism. In this study, the researchers used a qualitative approach with three main informant and the informant, the informant 3 primary is the father or the mother of an autistic child in accordance with predetermined criteria, while the informant was the one who advocates close to the parents of autistic children. Researchers visited the SLB to request data for parents who have a child with autism then enlisted the help of employees of SLB to contact informants, the informant selection techniques in this research is purposive sampling, based on characteristics that is parents who have autistic children and willing to become informants by filling the inform consent. Researchers using the method of semi structured interviews and observations as a means of collecting the appraisal. The result of this research shows that older people have autistic children experience a lack of understanding of the autistic child, experiencing the physical fatigue and low economic. Parents face the problem that arises in many ways there is a form of coping which successfully unfolds on this research, among others, coping with emotions that is based on the patient, coping with problems based on the parents bring to the doctor for a given therapy, autistic children send to the SLB, learn from the behavior of autistic children, teach and exemplifies the daily activities to autistic children, looking for work and rest when sick. Researchers can also uncover religious coping forms is resignation. Optimal or not coping with the chosen is influenced by age, gender, economic status, level of education and the environment.